High-adhesion overweight anticorrosive paint technology

By using modified polyarylethernitrile and MoS2@Zn-MOF derived carbon nanomaterials in the coating, combining polyamides and phenoamines epoxy curing agents, the traditional solution is to form high adhesion and corrosion-resistant super-heavy anticorrosion coatings. The problem of insufficient adhesion of the paint in extreme environments has achieved excellent protection effect on metal structures.

CN119320590AActive Publication Date: 2025-01-17刘嘉

Patent Information

Application Number
CN202411440796.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-17
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

Traditional anticorrosion coatings are difficult to provide adequate protection in extreme environments, especially in high humidity and high salt environments, where the adhesion of the coating decreases, resulting in accelerated metal corrosion. In addition, existing solvent-free coatings require adhesion and impact resistance. There is room for improvement in high situations.

Method used

By designing a special molecular structure and functional filler combination, a dense, dry and stable protective layer is formed to improve the adhesion between the coating and the substrate. Modified polyarylethernitrile and MoS2@Zn-MOF derived carbon nanomaterials are used. Combining polyamides and phenoamines epoxy curing agents, it forms an overweight anticorrosion coating with high adhesion and corrosion resistance.

Benefits of technology

It achieves excellent adhesion, corrosion resistance and high-strength protection in harsh environments. The coating adhesion can reach 12-42MPa. It has solvent-free, dew point limit, moisture resistance and long-term corrosion resistance, which significantly improves metals. The protective effect of the structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005086294060000081
    Figure BDA0005086294060000081
  • Figure BDA0005086294060000091
    Figure BDA0005086294060000091
Patent Text Reader

Abstract

The invention discloses a high-adhesion overweight anticorrosive paint technology, the overweight anticorrosive paint is composed of a component A and a component B. The component A comprises the following raw materials by weight: 40-60 parts of epoxy resin, 5-10 parts of modified polyarylene ether nitrile, 1-15 parts of a diluent, 1-10 parts of a functional filler, 1-15 parts of a pigment, and 0.1-3 parts of an auxiliary agent; the component B comprises the following raw materials in parts by weight: 5-25 parts of a polyamide epoxy curing agent, 5-25 parts of a phenolic aldehyde amine epoxy curing agent and 0.1-3 parts of an accelerant. Through reasonable combination of special molecular structure design and functional filler, a compact, dry and stable protective layer can be formed, and the adhesive force between the coating and a base material is remarkably improved, so that long-term effective protection is provided for a metal structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and in particular to a high-adhesion, super-heavy anti-corrosion coating technology. Background Art

[0002] With the development of industrialization, facilities such as steel structures, bridges, offshore platforms, petrochemical equipment, and ships are facing serious corrosion problems after long-term use in harsh environments. In particular, metal surfaces exposed to seawater, acidic and alkaline gases, salt spray, and damp heat are susceptible to corrosion, which can lead to reduced equipment performance, shortened service life, and even safety hazards. Therefore, anti-corrosion protection for these facilities has become an important issue that cannot be ignored in engineering.

[0003] Traditional anti-corrosion coatings, such as conventional epoxy coatings and polyurethane coatings, have certain anti-corrosion effects, but their corrosion resistance, adhesion and impact resistance are still limited when facing extreme environments. In particular, for facilities that are immersed in seawater for a long time or exposed to high humidity and high salt environments, conventional coatings are difficult to provide sufficient protection, resulting in coating failure, peeling, bubbles and other problems, which in turn accelerates metal corrosion.

[0004] In recent years, with the advancement of solvent-free epoxy coating technology, the environmental friendliness, thickness and corrosion resistance of the coating have been improved. However, the solvent-free coatings in the prior art still have room for improvement in situations where adhesion and impact resistance are required to be high. Especially when there is rust or moisture on the metal surface, the anti-corrosion effect of the coating is often limited, the adhesion of the coating decreases, and even peeling occurs. Therefore, it is necessary to develop an ultra-heavy anti-corrosion coating that can have excellent adhesion, corrosion resistance and high strength in harsh environments. Summary of the invention

[0005] Based on the problems existing in the background technology, the present invention provides a high-adhesion super-heavy anti-corrosion coating technology. Through the special molecular structure design and the reasonable combination of functional fillers, a dense, dry and stable protective layer can be formed, and the adhesion between the coating and the substrate can be significantly improved, thereby providing long-term and effective protection for the metal structure.

[0006] The present invention is implemented by the following technical solutions:

[0007] A high-adhesion, super-heavy anti-corrosion coating, consisting of component A and component B, wherein component A comprises the following raw materials in parts by weight: 40-60 parts of epoxy resin, 5-10 parts of modified polyarylethernitrile, 1-15 parts of diluent, 1-10 parts of functional filler, 1-15 parts of pigment, and 0.1-3 parts of additive;

[0008] Component B comprises the following raw materials in parts by weight: 5-25 parts of polyamide epoxy curing agent, 5-25 parts of phenolic amine epoxy curing agent, and 0.1-3 parts of accelerator.

[0009] Furthermore, the epoxy resin is at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, and novolac epoxy resin.

[0010] Furthermore, the preparation method of the modified polyarylethernitrile is specifically as follows: reactants 2,6-dichlorobenzonitrile, bisphenol A, and phenolphthalein are added to a reactor, the reactor is equipped with a stirrer, a condensing reflux tube, and a water separator, and a catalyst anhydrous potassium carbonate, a water-carrying agent toluene, and a solvent N-methylpyrrolidone are continuously added, the temperature is raised to 140-150° C. for azeotropic dehydration, and then toluene is evaporated, and the temperature is continuously raised to 190° C. The reaction enters a polymerization stage, and as the reaction proceeds, the viscosity of the solution system increases, and when the viscosity of the system becomes constant, the reaction is stopped, and the polymer is poured into a mixed solution of dilute hydrochloric acid and ethanol while hot, a large amount of white polymer solid is precipitated, the polymer solid is put into a grinder for crushing, and then repeatedly boiled with a large amount of hot water for purification, and the purified powder is dried to obtain the modified polyarylethernitrile.

[0011] Furthermore, the molar ratio of 2,6-dichlorobenzonitrile, bisphenol A and phenolphthalein is 1:(0.6-0.8):(0.2-0.4).

[0012] Furthermore, the diluent is ethylene glycol diglycidyl ether.

[0013] Furthermore, the functional filler is a MoS2@Zn-MOF derived carbon nanomaterial, and its preparation method comprises the following steps:

[0014] (1) Preparation of Zn-MOF: Zn(NO3)2·6H2O and 2-MeIM were dissolved in methanol solution respectively, and stirred vigorously. Then, the methanol solution containing 2-MeIM was slowly dropped into the methanol solution containing Zn(NO3)2·6H2O, stirred, allowed to stand, and centrifuged to collect the white product, which was washed with methanol several times. The white solid was dried in a vacuum oven to obtain the obtained Zn-MOF;

[0015] (2) Preparation of Zn-MOF derived carbon: Grind the white solid Zn-MOF into powder, put it into a tube furnace and calcine it at 800°C under N2 atmosphere to obtain black Zn-MOF derived carbon;

[0016] (3) Preparation of MoS2@Zn-MOF derived carbon: Zn-MOF derived carbon was dispersed in deionized water, and Na2MoO4·2H2O and CH4N2S were added for stirring and ultrasonic dissolution. The obtained solution was transferred to a stainless steel autoclave lined with polytetrafluoroethylene and subjected to solvothermal reaction at 200°C. After the reaction, the autoclave was naturally cooled to room temperature, the precipitate was collected by centrifugation, washed, and finally dried in a vacuum oven to obtain MoS2@Zn-MOF derived carbon nanomaterials.

[0017] Furthermore, the pigment is at least one of titanium dioxide, iron black powder, iron red powder, natural barium sulfate, precipitated barium sulfate, talcum powder, silicon dioxide ion exchange anti-rust pigment, and bentonite.

[0018] Furthermore, the auxiliary agent includes a dispersant, a defoamer, a leveling agent and a coupling agent, wherein the dispersant is an acrylic dispersant; the defoamer is an organic silicon defoamer; the leveling agent is an acrylic leveling agent; and the coupling agent is a silane coupling agent.

[0019] Furthermore, the curing accelerator is 2,4,6-tris(dimethylaminomethyl)phenol.

[0020] Furthermore, the weight ratio of component A to component B is 2-10:1.

[0021] Beneficial effects of the present invention:

[0022] (1) The high-adhesion, heavy-duty anticorrosive coating of the present invention has the following advantages: no solvent, no dew point restriction, high edge retention, extremely resistant to moisture, good compatibility with iron oxides attached to the surface, excellent adhesion on dry or wet steel surfaces, reaction with steel, wet oxidized surfaces, no strict requirements on surface roughness, longer construction time and long anticorrosion life. The high-adhesion, heavy-duty anticorrosive coating of the present invention has a super strong adhesion of 12-42MPa on dry and wet surfaces.

[0023] (2) The modified polyarylethernitrile is added to the high-adhesion super-heavy anti-corrosion coating of the present invention. The polyarylethernitrile has excellent mechanical strength, toughness and heat resistance, and can effectively improve the brittleness of the epoxy resin coating and effectively prevent the metal corrosion caused by the cracking failure of the epoxy coating due to stress concentration. The modified polyarylethernitrile introduces carboxylic acid side groups, which can form a stable cross-linked network structure with the epoxy resin through chemical bonds. The formation of such covalent bonds improves the cohesive strength of the coating and the adhesion between the coating and the substrate.

[0024] (3) The present invention introduces MoS2@Zn-MOF derived carbon nanomaterials, and the coating forms a highly dense barrier structure that can effectively prevent the penetration of moisture, oxygen and corrosive media. The corrosion inhibition of Zn combined with the lubricity and wear resistance of MoS2 enables the coating to still have a good protective effect in a long-term corrosive environment.

[0025] (4) The present invention adopts polyamide epoxy curing agent and phenolic amine epoxy curing agent. The molecular structure of polyamide curing agent contains more active hydrogen, groups that promote epoxy resin curing and hydrophobic groups, and has high reaction activity. The phenolic skeleton structure of phenolic amine epoxy curing agent can further improve the heat resistance and corrosion resistance of epoxy coating, and is particularly suitable for use in cold seasons or occasions with low ambient temperature. It can cure epoxy resin under environmental conditions such as about 0°C, 100% humid environment and underwater. DETAILED DESCRIPTION

[0026] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the following embodiments.

[0027] In the embodiments and comparative examples of the present invention, the epoxy resin is bisphenol A epoxy resin; the diluent is ethylene glycol diglycidyl ether; the pigment is iron oxide red powder; the dispersant is acrylic dispersant Sokalan CP9; the defoamer is silicone defoamer RP-6068 of Ruike Chemical; the leveling agent is acrylic leveling agent BYK358N; the coupling agent is silane coupling agent KH560; the polyamide epoxy curing agent DEH140; the phenolic amine epoxy curing agent T31; and the curing accelerator is 2,4,6-tris(dimethylaminomethyl)phenol.

[0028] Example 1

[0029] A high-adhesion, super-heavy anti-corrosion coating, consisting of component A and component B, wherein component A comprises the following raw materials in parts by weight: 50 parts of epoxy resin, 15 parts of modified polyarylethernitrile, 6 parts of diluent, 5 parts of functional filler, 10 parts of pigment, 0.5 parts of dispersant, 0.3 parts of defoamer, 0.5 parts of leveling agent and 1.0 parts of coupling agent;

[0030] Component B includes the following raw materials in parts by weight: 15 parts of polyamide epoxy curing agent, 10 parts of phenolic amine epoxy curing agent, and 1.0 part of accelerator.

[0031] The weight ratio of component A to component B is 2:1.

[0032] The preparation method of the modified polyarylethernitrile is as follows: reactants 2,6-dichlorobenzonitrile, bisphenol A and phenolphthalein are added into a reactor in a molar ratio of 1:0.7:0.3, the reactor is equipped with a stirrer, a condensing reflux pipe and a water separator, and a catalyst anhydrous potassium carbonate, a water-carrying agent toluene and a solvent N-methylpyrrolidone are continuously added, the temperature is raised to 140-150°C for azeotropic dehydration, the toluene is then evaporated, the temperature is continuously raised to 190°C, the reaction enters a polymerization stage, as the reaction proceeds, the viscosity of the solution system increases, the reaction is stopped when the viscosity of the system becomes constant, the polymer is poured into a mixed solution of dilute hydrochloric acid and ethanol while hot, a large amount of white polymer solid is precipitated, the polymer solid is put into a grinder for crushing, and then repeatedly boiled with a large amount of hot water for purification, and the purified powder is dried to obtain the modified polyarylethernitrile.

[0033] The functional filler is a MoS2@Zn-MOF derived carbon nanomaterial, and the preparation method thereof comprises the following steps:

[0034] (1) Preparation of Zn-MOF: 2.5 parts of Zn(NO3)2·6H2O and 3.382 parts of 2-MeIM were dissolved in 150 parts of methanol solution respectively, and stirred vigorously. Then, the methanol solution containing 2-MeIM was slowly dripped into the methanol solution containing Zn(NO3)2·6H2O, stirred for 4 hours, allowed to stand, and the white product was collected by centrifugation. It was washed with methanol several times, and the white solid was dried in a vacuum oven to obtain Zn-MOF;

[0035] (2) Preparation of Zn-MOF derived carbon: Grind the white solid Zn-MOF into powder, put it into a tube furnace and calcine it at 800°C under N2 atmosphere to obtain black Zn-MOF derived carbon;

[0036] (3) Preparation of MoS2@Zn-MOF derived carbon: 3.2 parts of Zn-MOF derived carbon were dispersed in deionized water, 14.4 parts of Na2MoO4·2H2O and 17.1 parts of CH4N2S were added, stirred and dissolved by ultrasonication. The obtained solution was transferred to a stainless steel autoclave lined with polytetrafluoroethylene and subjected to solvothermal reaction at 200°C. After the reaction, the autoclave was naturally cooled to room temperature, the precipitate was collected by centrifugation, washed, and finally dried in a vacuum oven to obtain MoS2@Zn-MOF derived carbon nanomaterials.

[0037] Example 2

[0038] The difference from Example 1 is that component A includes the following raw materials in parts by weight: 50 parts of epoxy resin, 10 parts of modified polyarylethernitrile, 6 parts of diluent, 5 parts of functional filler, 10 parts of pigment, 0.5 parts of dispersant, 0.3 parts of defoamer, 0.5 parts of leveling agent and 1.0 parts of coupling agent.

[0039] The rest is the same as in Example 1.

[0040] Example 3

[0041] The difference from Example 1 is that component A includes the following raw materials in parts by weight: 50 parts of epoxy resin, 15 parts of modified polyarylethernitrile, 6 parts of diluent, 8 parts of functional filler, 10 parts of pigment, 0.5 parts of dispersant, 0.3 parts of defoamer, 0.5 parts of leveling agent and 1.0 parts of coupling agent.

[0042] The rest is the same as in Example 1.

[0043] Comparative Example 1

[0044] The difference from Example 1 is that component A includes the following raw materials in parts by weight: 50 parts of epoxy resin, 6 parts of diluent, 5 parts of functional filler, 10 parts of pigment, 0.5 parts of dispersant, 0.3 parts of defoamer, 0.5 parts of leveling agent and 1.0 parts of coupling agent.

[0045] The rest is the same as in Example 1.

[0046] Comparative Example 2

[0047] The difference from Example 1 is that component A includes the following raw materials in parts by weight: 50 parts of epoxy resin, 15 parts of poly(arylene ether nitrile), 6 parts of diluent, 5 parts of functional filler, 10 parts of pigment, 0.5 parts of dispersant, 0.3 parts of defoamer, 0.5 parts of leveling agent and 1.0 parts of coupling agent.

[0048] The rest is the same as in Example 1.

[0049] Comparative Example 3

[0050] The difference from Example 1 is that the preparation method of the modified polyarylether nitrile is specifically as follows: reactants 2,6-dichlorobenzonitrile, bisphenol A, and phenolphthalein are added to a reactor in a molar ratio of 1:0.5:0.5, the reactor is equipped with a stirrer, a condensing reflux tube, and a water separator, and a catalyst anhydrous potassium carbonate, a water-carrying agent toluene, and a solvent N-methylpyrrolidone are continuously added, the temperature is raised to 140-150° C. for azeotropic dehydration, and then toluene is evaporated, and the temperature is continuously raised to 190° C. The reaction enters the polymerization stage, and as the reaction proceeds, the viscosity of the solution system increases, and the reaction is stopped when the viscosity of the system becomes constant, and the polymer is poured into a mixed solution of dilute hydrochloric acid and ethanol while hot, a large amount of white polymer solid is precipitated, the polymer solid is put into a grinder for crushing, and then repeatedly boiled with a large amount of hot water for purification, and the purified powder is dried to obtain the modified polyarylether nitrile.

[0051] The rest is the same as in Example 1.

[0052] Comparative Example 4

[0053] The difference from Example 1 is that component A includes the following raw materials in parts by weight: 50 parts of epoxy resin, 15 parts of modified polyarylethernitrile, 6 parts of diluent, 10 parts of pigment, 0.5 parts of dispersant, 0.3 parts of defoamer, 0.5 parts of leveling agent and 1.0 parts of coupling agent.

[0054] The rest is the same as in Example 1.

[0055] Comparative Example 5

[0056] The difference from Example 1 is that the functional filler is MoS2@Zn-MOF nanomaterial, and its preparation method comprises the following steps:

[0057] (1) Preparation of Zn-MOF: 2.5 parts of Zn(NO3)2·6H2O and 3.382 parts of 2-MeIM were dissolved in 150 parts of methanol solution respectively, and stirred vigorously. Then, the methanol solution containing 2-MeIM was slowly dripped into the methanol solution containing Zn(NO3)2·6H2O, stirred for 4 hours, allowed to stand, and the white product was collected by centrifugation. It was washed with methanol several times, and the white solid was dried in a vacuum oven to obtain Zn-MOF;

[0058] (2) Preparation of MoS2@Zn-MOF: 3.2 parts of Zn-MOF were dispersed in deionized water, and 14.4 parts of Na2MoO4·2H2O and 17.1 parts of CH4N2S were added, stirred, and dissolved by ultrasonication. The obtained solution was transferred to a stainless steel autoclave lined with polytetrafluoroethylene and subjected to solvothermal reaction at 200°C. After the reaction, the autoclave was naturally cooled to room temperature, the precipitate was collected by centrifugation, washed, and finally dried in a vacuum oven to obtain MoS2@Zn-MOF nanomaterials.

[0059] Specifically, a patch that does not react with the solution is placed at the bottom of the inner side of the container for collecting the precipitate by centrifugation.

[0060] Preferably, the patch is fixed to the inner bottom of the container, and the color of the patch is selected based on the color of the solution; if the color of the solution is light, the color of the patch is black; if the color of the solution is dark, the color of the patch is white.

[0061] Specifically, the patch in the test solution is photographed by a camera arranged on the top of the container, and the photographed image is processed, the edge graphics of the image are processed based on the edge detection algorithm, and the background is filled according to the seed filling algorithm. The image is segmented to obtain multiple areas, and the segmented areas are marked and merged.

[0062] Preferably, according to the edge contour extraction, the quasi-coordinates of the target area corresponding to the patch are obtained, and the gray value of the patch in the quasi-coordinates of the target area, the gray value of the background with the same area as the patch, and the gray value of the precipitation area are calculated respectively, wherein the gray value is calculated as follows:

[0063] Gray=0.299R+0.578G+0.114B

[0064] Among them, R, G, and B respectively represent the values ​​of the three colors red, green, and blue in the image based on the RGB standard.

[0065] Subsequently, the Euclidean distance is used as a measure of the difference between the grayscale value of the patch in the target area and the grayscale value of the background of the same area, and the turbidity of the tested solution is determined from this.

[0066]

[0067] Wherein, T is the turbidity of the target solution; dex and y are the horizontal and vertical coordinates; n and m are the image pixel sizes; g is the gray value of the patch; and g' is the gray value of the background of the same area.

[0068] Specifically, according to the calculated turbidity of the target solution, it is determined whether the preset condition is met, thereby controlling the stopping or maintaining of the centrifugal operation.

[0069] Preferably, when the turbidity of the target solution is less than a preset turbidity threshold, it is determined that the preset condition is met, and the centrifugal device is controlled to stop the centrifugal operation; when the turbidity of the target solution is not less than the preset turbidity threshold, it is determined that the preset condition is not met, and the centrifugal device is controlled to continue the centrifugal operation.

[0070] Preferably, the turbidity of the target solution is detected based on a preset time interval to control the centrifugation operation; wherein the preset time interval is determined according to actual needs and is not limited here.

[0071] Furthermore, after the centrifugal operation is stopped, the edge of the precipitation area is determined by using Canny edge detection, and the RGB color vector of the precipitation area is obtained to calculate the grayscale value of the precipitation area; for the edge of the precipitation area, the number of acute angles on the edge is determined, and the average number of acute angles per unit length is further calculated. If the average number of acute angles per unit length is greater than a preset number, it is determined that the edge of the precipitation area is not smooth; if the average number of acute angles per unit length is not greater than a preset number, it is determined that the edge of the precipitation area is smooth;

[0072] Furthermore, judging whether the grayscale value of the precipitation area is greater than a preset grayscale value;

[0073] When the edge of the sedimentation area is smooth and the grayscale value is greater than the preset grayscale value, it is determined that the sedimentation effect meets the collection requirements and the collection operation is performed; otherwise, the person determining the effect needs to perform centrifugation and sedimentation operations.

[0074] Test example

[0075] The anticorrosive coatings prepared in Examples 1-3 and Comparative Examples 1-5 were subjected to performance tests, and the test items and methods are as follows:

[0076] Adhesion test (wet surface, dry surface) (unit: MPa): ASTM standard D4541

[0077] Abrasion resistance (unit: g / week (1000 weeks / 1kg)): ASTM D4060

[0078] Impact resistance (unit: KgF / cm 2 ): ASTM D4060

[0079] Maximum elongation (in %): ISO / R527

[0080] Compressive strength (unit: KgF / cm 2 ): ISO 844

[0081] Bending strength (unit: KgF / cm 2 ): ISO 178

[0082] Condensation resistance (unit: h): ASTM standard D4585

[0083] Water absorption (unit: %): ASTM standard D570

[0084] Salt spray resistance (unit: h): ASTM standard B117

[0085] Salt water (6% NaCl) immersion (in hours): ASTM standard D870

[0086] Soaking in alkali solution (40% NaOH) (in hours): ASTM standard D870

[0087] Acid (30% sulfuric acid) immersion (hours): ASTM standard D870

[0088] The test results are shown in Table 1.

[0089] Table 1

[0090]

[0091] It can be seen from the results in Table 1 that the adhesion (dry surface) of the high-adhesion super-heavy anti-corrosion coating prepared by the present invention can reach up to 42 MPa; at the same time, it also has excellent mechanical properties, wear resistance, impact resistance, acid and alkali resistance, salt spray resistance and salt water resistance.

[0092] Comparative Example 1 does not contain polyarylethernitrile, and directly uses epoxy resin to prepare anticorrosive coating. Epoxy resin has certain adhesion on dry surface, but it is easy to peel off on wet or complex surface, and the long-term stability of coating is poor. In addition, epoxy resin is relatively brittle and has poor impact resistance, and it is easy to crack or fall off when subjected to external force or impact. Epoxy resin is relatively brittle and has poor impact resistance, and it is easy to crack or fall off when subjected to external force or impact. In the case of large temperature changes, epoxy resin coating is prone to thermal expansion and contraction, resulting in cracking or peeling of coating.

[0093] In comparative example 2, polyarylether nitrile is directly used, and carboxylic acid-containing side groups are not introduced. It can be seen from the data in Table 1 that compared with the anticorrosive coating in comparative example 1, the overall performance has been significantly improved. Polyarylether nitrile has excellent mechanical strength, toughness and heat resistance, and can effectively improve the brittleness problem of epoxy resin coating, and effectively prevent the metal corrosion phenomenon caused by the failure of epoxy coating due to stress concentration cracking. Polyarylether nitrile has high permeability resistance and hydrophobicity, which makes it possible to be used as an effective physical barrier to prevent moisture and corrosive media (such as water, oxygen, chloride ions, etc.) from penetrating into the coating interior and metal surface. Compared with epoxy resin, the water absorption rate of polyarylether nitrile is low, which means that in a humid or high humidity environment, it can better maintain the integrity of the coating and avoid the absorption and diffusion of moisture. Although epoxy resin itself has good anticorrosive properties, it may cause coating degradation due to water absorption and penetration when it is exposed to corrosive environments such as moisture and salt spray for a long time. By adding polyarylether nitrile, the anti-permeability of epoxy resin can be improved, and the diffusion of corrosive media can be further delayed, effectively extending the corrosion protection cycle of coating.

[0094] Although modified polyarylether nitrile is used in Comparative Example 3, the molar ratio of bisphenol A and phenolphthalein in the modified polyarylether nitrile is adjusted, and the amount of carboxyl side groups introduced is increased. The introduction of carboxyl groups as side chain groups can increase the polarity of polyarylether nitrile and increase its application potential in coatings. Carboxyl groups can chemically bond with various metal surfaces, increase the adhesion of the coating to the substrate, and may also improve the water resistance and corrosion resistance of the coating. However, excessive carboxyl groups are prone to react with moisture or other chemicals in the environment, which will cause the polymer to degrade or age in a humid or corrosive environment, affecting the stability of the coating.

[0095] MoS2@Zn-MOF derived carbon nanomaterials were not used in Comparative Example 4, and the performance of the coating was significantly reduced compared to that in Example 1. MoS2@Zn-MOF derived carbon nanomaterials have excellent lubricity and dispersibility, and can effectively improve the interfacial bonding between the coating and the substrate. MoS2@Zn-MOF derived carbon nanomaterials have strong hydrophobic properties and shielding effects, which can reduce the absorption of water by the coating. MoS2@Zn-MOF derived carbon nanomaterials have excellent corrosion resistance, can block the penetration of corrosive media, and improve the durability of the coating in acids, alkalis, salt spray and various solvents.

[0096] In Comparative Example 5, MoS2@Zn-MOF nanomaterials were used, and Zn-MOF was not carbonized, which resulted in problems with the long-term stability of Zn-MOF in a corrosive environment. However, the carbonized Zn-MOF was able to form a stable skeleton structure. 2+ It also provides additional protection for corrosion inhibition. Combining the corrosion resistance and lubricity of MoS2, the composite structure of MoS2@Zn-MOF derived carbon is more stable in the coating.

[0097] Finally, it should be noted that the above-mentioned embodiments only express several implementation methods of the present invention and are not intended to limit the invention. For those skilled in the art, any modification, equivalent replacement, improvement, etc. made without departing from the concept of the present invention should be included in the protection scope of the invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A high-adhesion, super-heavy anti-corrosion coating, characterized in that: It consists of two parts, component A and component B, wherein component A includes the following raw materials in parts by weight: 40-60 parts of epoxy resin, 5-10 parts of modified polyarylethernitrile, 1-15 parts of diluent, 1-10 parts of functional filler, 1-15 parts of pigment, and 0.1-3 parts of additive; Component B comprises the following raw materials in parts by weight: 5-25 parts of polyamide epoxy curing agent, 5-25 parts of phenolic amine epoxy curing agent, and 0.1-3 parts of accelerator.

2. The high-adhesion, super-heavy anti-corrosion coating according to claim 1, characterized in that: The epoxy resin is at least one of bisphenol A epoxy resin, bisphenol F epoxy resin and novolac epoxy resin.

3. The high-adhesion, super-heavy anti-corrosion coating according to claim 1, characterized in that: The preparation method of the modified polyarylether nitrile is specifically as follows: reactants 2,6-dichlorobenzonitrile, bisphenol A and phenolphthalein are added into a reactor, the reactor is equipped with a stirrer, a condensation reflux pipe and a water separator, anhydrous potassium carbonate as a catalyst, toluene as a water-carrying agent and N-methylpyrrolidone as a solvent are continuously added, the temperature is raised to 140-150°C for azeotropic dehydration, toluene is subsequently evaporated, the temperature is continuously raised to 190°C, the reaction enters a polymerization stage, the viscosity of the solution system increases with the progress of the reaction, the reaction is stopped when the viscosity of the system is constant, the polymer is poured into a mixed solution of dilute hydrochloric acid and ethanol while hot, a large amount of white polymer solid is precipitated, the polymer solid is put into a pulverizer for pulverization, and then a large amount of hot water is used for repeated boiling for purification, and the purified powder is dried to obtain the modified polyarylether nitrile.

4. The high-adhesion, super-heavy anti-corrosion coating according to claim 3, characterized in that: The molar ratio of 2,6-dichlorobenzonitrile, bisphenol A and phenolphthalein is 1:(0.6-0.8):(0.2-0.4).

5. The high-adhesion, super-heavy anti-corrosion coating according to claim 1, characterized in that: The diluent is ethylene glycol diglycidyl ether.

6. The high-adhesion, super-heavy anti-corrosion coating according to claim 1, characterized in that: The functional filler is a MoS2@Zn-MOF derived carbon nanomaterial, and the preparation method thereof comprises the following steps: (1) Preparation of Zn-MOF: Zn(NO3)2·6H2O and 2-MeIM were dissolved in methanol solution respectively, stirred vigorously, and then the methanol solution containing 2-MeIM was slowly dropped into the methanol solution containing Zn(NO3)2·6H2O, stirred, allowed to stand, and centrifuged to collect the white product, which was washed with methanol several times. The white solid was dried in a vacuum oven to obtain Zn-MOF; (2) Preparation of Zn-MOF derived carbon: Grind the white solid Zn-MOF into powder, put it into a tube furnace and calcine it at 800°C under N2 atmosphere to obtain black Zn-MOF derived carbon; (3) Preparation of MoS2@Zn-MOF derived carbon: Zn-MOF derived carbon was dispersed in deionized water, and Na2MoO4·2H2O and CH4N2S were added for stirring and ultrasonic dissolution. The obtained solution was transferred to a stainless steel autoclave lined with polytetrafluoroethylene and subjected to solvothermal reaction at 200°C. After the reaction, the autoclave was naturally cooled to room temperature, the precipitate was collected by centrifugation, washed, and finally dried in a vacuum oven to obtain MoS2@Zn-MOF derived carbon nanomaterials.

7. The high-adhesion, super-heavy anti-corrosion coating according to claim 1, characterized in that: The pigment is at least one of titanium dioxide, iron black powder, iron red powder, natural barium sulfate, precipitated barium sulfate, talcum powder, silicon dioxide ion exchange type anti-rust pigment and bentonite.

8. The high-adhesion, super-heavy anti-corrosion coating according to claim 1, characterized in that: The additives include dispersants, defoamers, leveling agents and coupling agents, wherein the dispersants are acrylic dispersants; the defoamers are silicone defoamers; the leveling agents are acrylic leveling agents; and the coupling agents are silane coupling agents.

9. The high-adhesion, super-heavy anti-corrosion coating according to claim 1, characterized in that: The curing accelerator is 2,4,6-tris(dimethylaminomethyl)phenol.

10. The high-adhesion, super-heavy anti-corrosion coating according to claim 1, characterized in that: The weight ratio of component A to component B is 2-10:1.

Citation Information

Patent Citations

  • Preparation method of high-performance carboxyl functionalized poly (arylene ether nitrile)

    CN109503826A

  • Graphene anticorrosive primer for heat exchanger in marine environment and preparation method thereof

    CN111393950A

  • Corrosion-resistant chromium-free coating and surface treatment process thereof

    CN111690324A

  • Preparation method of wallpaper capable of adsorbing and purifying air

    CN112208191A

  • Polyaniline / MOF composite coating electrode material as well as preparation method and application thereof

    CN112500760A

Cited By

  • MXene-Ni-C-ODD, corrosion-resistant modified waterborne epoxy resin coating prepared from MXene-Ni-C-ODD and application

    CN120383837A